Export and firms' performance in North Macedonia: self selection or learning by doing? - Biljana Jovanovic (National Bank of the Republic of North Macedonia, 2020)
Export is an important contributor to growth with numerous direct and indirect macroeconomic benefits. Moreover, firms engaged in exporting activity tend to have superior characteristics compared to their non-exporting peers. The paper is focused on identifying reasons behind this superiority of exporters by testing two hypothesis - self-selection and learning by doing hypothesis. The analysis is done on a sample of over 1,900 manufacturing firms annually, for the period 2013-2017. In line with previous empirical research, we found evidence in favor of the self-selection hypothesis. This means that more successful and more productive firms become exporters as a result of their performance i.e. they self-select themselves in the international market. In addition, our results suggest that, complementary to the self-selection process, there are some evidence of the validity of learning by doing hypothesis.
Keywords: D24; D22; F14; 330; self selection; learning by doing; export; matching